Including a symposium on Mary Morgan : curiosity, imagination, and surprise - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Emerald Publishing Limited, 2018)
Volume 36B of Research in the History of Economic Thought and Methodology features a symposium reflecting on the significance of Mary Morgan's contributions to the history and philosophy of economics. Symposium participants include guest editors Marcel Boumans and Hsiang-Ke Chao, as well as Harro Maas, Tiago Mata, Gerardo Serra, and Andrej Svorenčík. The volume also features the next installment of Charles R. McCann, Jr. and Vibha Kapuria-Foreman's continuing project on the neglected Chicago economist, Robert Franklin Hoxie.
Includes index.
Keywords: Economics -- History -- Congresses.; Economics -- Methodology -- Congresses.; Morgan, Mary S. -- Congresses.; Women economists -- Great Britain -- Congresses.; Business & Economics -- General.; Economics, finance, business & management.; elektronické knihy; electronic books